An analysis of the English textbook “think” to the curriculum 2013 - Fina Sakinah Mawaddah; Farida Hamid; Syauki Syauki (Jurnal Pendidikan, Sains Sosial, dan Agama, 2023)
The study aimed to evaluate the relevance of materials in the textbook "Think" with basic competencies of the English curriculum 2013. The analysis has been done in interpersonal, transactional, and special function text genres. The instrument of the research was the checklist evaluation. The textbook was analyzed using a qualitative research method with a content analysis design. The data collection procedures started from perusing, highlighting, eliciting, grouping, coding, and tabulating. Then, the data was analyzed by adapting the procedures from Miles, Huberman, and Saldaña (2014) using data selecting, data display, data interpreting, and conclusion. The data was evaluated using the categories of complete, slightly complete, slightly incomplete, and null. In the textbook, 12 materials were checked for relevance to the English curriculum 2013. The result of the study showed that the textbook only meets ten materials out of 22 materials suggested in basic competence 3 and 4 of English curriculum 2013. The interpersonal genre text does not have any related material out of three materials from one indicator. for the transactional genre text, the book has two complete indicators that suit the textbook and syllabus of curriculum 2013. It has one slightly complete and one slightly incomplete indicator. For the special text, the book does not meet any of the material suggested by the syllabus of curriculum 2013. The result found that the level of conformity of the "Think" textbook is slightly incomplete because the textbook contains materials that are not suggested by the syllabus. To sum up, the textbook "Think" is better to be used as a supplementary book in school with curriculum 2013. The book has various activities inside to support the teaching and learning process.